Optimalisasi Pengelolaan Akun dan Konten Media Sosial Youtube di Masjid Al Mishbah, Gedongan, Trirenggo, Kabupaten Bantul - Ari Sugiharto; Satyo Nuryadi; Al Musa Karim (Universitas Teknologi Yogyakarta, 2024)
Social media account management is among the major aspects to manage religious activities at any mosque. Social media (is) well known as an effective medium for disseminating information. For religious activity, for example a mosque community, shifting the method of documenting, from computer file to social media posts, (that) has made the religious activities reached more viewers. Moreover, the application of social media in a mosque community activities seemingly grow attention from the young believers and local activist as they are digital natives, to be engaged more to various activities on the mosque. Al Mishbah, one of a mosque in Trirenggo, Kabupaten Bantul had run an Youtube channel for several months. Some religious contents such as preaches, or other social religious activities have been uploaded. On term of content, the quality of the video used, relatively standard. Though, the account still need to be optimalized to make it more interesting for the viewers. Help from external stakeholder such as academic society still broadly needed. Using discussion and workshop method, our team from Universitas Teknologi Yogyakarta, giving assistance to this community, especially the social media team from Al Mishbah, to improve the productivity of the already run Youtube channel. As the result, a certain strategy had been set, that shorts Youtube video and live streaming must be produce more with better qualities within this Youtube account.